A General Model of Neutrosophic Ideals in BCK/BCI-algebras Based on Neutrosophic Points - Bordbar, Hashem; Borzooei, Rajab Ali; Smarandache, Florentin; Jun, Young Bae (Bulletin of the Section of Logic, 2020)
More general form of (∈, ∈ ∨q)-neutrosophic ideal is introduced, and their properties are investigated. Relations between (∈, ∈)-neutrosophic ideal and (∈, ∈ ∨q(kT ,kI ,kF ))-neutrosophic ideal are discussed. Characterizations of (∈, ∈∨q(kT ,kI,kF ))-neutrosophic ideal are discussed, and conditions for a neutrosophic set to be an (∈, ∈∨q(kT ,kI ,kF ))-neutrosophic ideal are displayed.